Outcomes of prolonged and low-dose ciclosporin in an Asian population. (19th May 2021) - Choi, Ellie; Cook, Alex; Phuan, Crystal; Martin, Aaron; Yang, Sam; Aw, Derrick; Chandran, Nisha Suyien
Abstract: Background: Ciclosporin is used in dermatology for a variety of conditions. Existing guidelines commonly recommend a starting dose of 3–5 mg/kg/day. Objectives: We sought to assess response in our cohort of patients in whom lower doses of ciclosporin were used, and compare the efficacy and side effect profile with existing literature. Methods: We retrospectively studied the use of ciclosporin (cyclosporine A) in our dermatological center. Ciclosporin dose trajectories and changes in disease severity were analyzed. Results: 92 patients were studied (64 with eczema, 17 with psoriasis). Mean initiation ciclosporin dose was relatively low at 1.53 mg/kg/day, with an increase to a mean of 2.61 mg/kg/day at 6 months. The median duration of treatment was 180 days (range 3–2160 days, IQR 383). The response was seen as early as 2 weeks, with greatest control of disease at 6 months. 32 patients were on ciclosporin for a period of 1 year or longer, of whom only 1 had a greater than 30% increase in creatinine that crossed the upper limit of normal. Conclusion: In our population, a lower dose likely resulted in a slower peak to greatest control, but was well tolerated with minimal renal impairment despite a relatively long average period of use.